Students and lecturers experiences in courses provided for the English thesis defense examinations - Iskandar Abdul Samad; Siti Sarah Fitriani; Singhanat Nomnian; Syamsul Bahri Ys; Sofia Sofia (Universitas Syiah Kuala, 2024)
Thesis Defense Examination (TDE) is an assessment that most undergraduate students around the world have to pass in order to graduate from universities. Some students can pass the examination satisfactorily, while others fail due to their poor performance. In the EFL general context, the issue of poor performance of undergraduate students in the TDE conducted in English is a piece of common knowledge among lecturers as the examiners and students as the examinees. Within the Indonesian context, this study aims at investigating students and lecturers experiences in Research Methodology (RM) (focusing on written competence) and Seminar on ELT (SoELT) (focusing on oral competence) courses, where the case was taken from the English Education Department of a public university located in Banda Aceh, Indonesia. By using a purposive sampling technique, we involved five students who have passed RM and SoELT, two lecturers who teach RM, and two lecturers who teach SoELT as the participants in this qualitative research. Interviews were employed to gather the data to address the investigation. We consulted Hyland (2004) for the analysis of the teaching and learning of written competence, and Alptekin (2002) to analyze the teaching and learning of oral competence in classroom activities. The results of the analysis show that there are matches and mismatches between what was experienced by the students and what the lecturers experienced. We also found that some activities in the courses hindered students from being competent in their performance in TDE.